Congenital Lobar Emphysema with Pulmonary Extramedullary Hematopoiesis - Kishor SURYAWANSHI; Dhiraj NIKUMBH; Sudhir SINGHAVI; Rajshri DAMLE; Nandkumar DRAVID (Federation of Turkish Pathology Societies, 2017)
Congenital lobar emphysema is a one of the rare variety of congenital abnormality of the lung causing respiratory distress in newborns and infants. Herein, we report a case of congenital lobar emphysema in a 3-week-old female admitted to the pediatric intensive care unit with severe respiratory distress. CT scan revealed a hyperinflated, hyperlucent left upper lobe, collapse of the ipsilateral lung and marked mediastinal shift to the right. The patient underwent emergency left upper lobectomy with improvement of her condition in the postoperative period. Histopathological findings confirmed the clinical diagnosis of congenital lobar emphysema with an unusual finding of pulmonary extramedullary hematopoiesis. Congenital lobar emphysema often presents a diagnostic and therapeutic dilemma and therefore requires a high index of suspicion in neonates presenting with respiratory distress to avoid morbidity and mortality.